On the way from straddled to stretched Tkatchev on high bar - Naundorf, F.; Brehmer, S.; Lehmann, T.; Seidel, I. (ISBS - Conference Proceedings Archive (Konstanz), 2012)
Reversing the direction of rotation is the main issue for the flight element Tkatchev on high bar. The principles are well described. There is a lack of knowledge to apply this to motor learning. Aim of the study is to analyse an individual gymnast`s performance and support the change from straddled to stretched Tkatchev. An instrumented high bar (force measurement) was used to give the gymnast immediately feedback about the performance. The gymnast was informed about the magnitude of the force maxima during the preparatory giant swing. After 5 training sessions with 42 trails the gymnast transferred more energy (higher forces) to the bar. But this results not in a higher angular momentum during the Tkatchev flight. Possible causes for this result where discussed. The complex demands on energy transfer and precise performance are important.